2023
DOI: 10.1007/s00204-023-03527-y
|View full text |Cite
|
Sign up to set email alerts
|

Duplex sequencing provides detailed characterization of mutation frequencies and spectra in the bone marrow of MutaMouse males exposed to procarbazine hydrochloride

Abstract: Mutagenicity testing is an essential component of health safety assessment. Duplex Sequencing (DS), an emerging high-accuracy DNA sequencing technology, may provide substantial advantages over conventional mutagenicity assays. DS could be used to eliminate reliance on standalone reporter assays and provide mechanistic information alongside mutation frequency (MF) data. However, the performance of DS must be thoroughly assessed before it can be routinely implemented for standard testing. We used DS to study spo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 42 publications
3
5
0
Order By: Relevance
“…Comparison of our results with the published studies in which the same TwinStrand mouse mutagenesis panel was used, revealed both similarities and differences. Analogous to results of the current investigation, targets on chr13 and chr19 accumulated relatively low levels of mutations in bone marrow of MutaMouse following exposure to either benzo(a)pyrene ( 49 ) or procarbazine hydrochloride ( 56 ). The intergenic target on chr14 was heavily loaded with mutations in all three cases.…”
Section: Discussionsupporting
confidence: 70%
“…Comparison of our results with the published studies in which the same TwinStrand mouse mutagenesis panel was used, revealed both similarities and differences. Analogous to results of the current investigation, targets on chr13 and chr19 accumulated relatively low levels of mutations in bone marrow of MutaMouse following exposure to either benzo(a)pyrene ( 49 ) or procarbazine hydrochloride ( 56 ). The intergenic target on chr14 was heavily loaded with mutations in all three cases.…”
Section: Discussionsupporting
confidence: 70%
“…In this analysis, we report unique mutations only; mutations appearing more than once in the same sample were assumed to have arisen from clonal expansion and were thus counted as one mutation, which may guard against over-estimating the MF. 49 Of note, 96% of all SNV mutations (with a VAF < 1%) and 70% of non-SNV mutations were single count (non-clonal) mutations, respectively.…”
Section: Resultsmentioning
confidence: 96%
“…Under this assumption, all identical mutations within a sample were counted as one single mutation to calculate the minimum mutation frequency (MFmin). We also counted all mutations to obtain the maximum mutation frequency (MFmax) (25). The variant allele fraction was set to 0.01 to exclude mosaicism and germline mutations.…”
Section: Ds Data Interpretation and Statistical Analysismentioning
confidence: 99%
“…Modern next-generation sequencing (NGS) technologies paired with error-correcting processes provide opportunities to comprehensively characterize mutagenesis (22). Duplex Sequencing (DS) is a targeted error-corrected NGS technology that allows the detection of rare mutations (23,24,25,26). It reduces the technical error rate of conventional NGS by uniquely tagging both strands of the original DNA fragments during library building, enabling the development of consensus sequences for each strand to eliminate PCR and sequencing errors (22,27,28).…”
Section: Introductionmentioning
confidence: 99%